Conceptual Frameworks of Sustainable Urban Development: Proposals for Local Development - Kantaros, Nattapong; Santivong, Amarita; Chumphonwong, Tapanee; Tistueng, Kingkaew; Lomon, Thanupong (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
This academic article aims to explain the conceptual framework for urban development, focusing on the integration of sustainable and concepts and highlighting the role of local administrative organizations as a key mechanism in driving urban development in accordance with the context of Thai society. A review and synthesis of urban development concepts in terms of sustainability at the local level. This review indicates that development with clear goals and systematic implementation can maximize resource efficiency while enhancing the quality of life for citizens across physical, economic, social, and environmental dimensions. Sustainably developed cities can reduce inequality and promote equitable access to basic services. Moreover, urban development should consider the connectivity and alignment between cities and local administrative organizations, while considering the specific context of each area. The key proposal of this article is that genuine decentralization of power to local administrative organizations should be pursued, enabling them to effectively and sustainably define, plan, and implement urban development according to the unique characteristics of their areas.